A novel Noonan syndrome RAF1 mutation: lethal course in a preterm infant - Ana Ratola; Helena Moreira Silva; Ana Guedes; Céu Mota; Ana Cristina Braga; Dulce Oliveira; Artur Alegria; Carmen Carvalho; Sílvia Álvares; Elisa Proença (MDPI AG, 2015)
Noonan syndrome is a relatively common and heterogeneous genetic disorder, associated with congenital heart defect in about 50% of the cases. If the defect is not severe, life expectancy is normal. We report a case of Noonan syndrome in a preterm infant with hypertrophic cardiomyopathy and lethal outcome associated to acute respiratory distress syndrome caused by Adenovirus pneumonia. A novel mutation in the RAF1 gene was identified: c.782C>G (p.Pro261Arg) in heterozygosity, not described previously in the literature. Consequently, the common clinical course in this mutation and its respective contribution to the early fatal outcome is unknown. No conclusion can be established regarding genotype/phenotype correlation.